2006
DOI: 10.2118/06-04-02
|View full text |Cite
|
Sign up to set email alerts
|

Should You Trust Your Heavy Oil Viscosity Measurement?

Abstract: Heavy oil viscosity is one of the few criteria available to help predict if cold production will give economic rates, or if thermal processes will be required to reduce the oil viscosity to achieve the required rates. If cold production is selected, viscosity is again used to help determine whether vertical or horizontal wells should be used. Viscosity data are also used to adjust cold production exploitation strategies if the production rates are significantly lower than expected. Petrovera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The accuracy and repeatability of VR viscosity measurements are affected by the selection of viscometers and the experimental procedures followed by different operators [4,36]. A study published by Miller et al [4] indicated that heavy oil viscosities measured by different viscometers, or by the same type of viscometer but measured in different laboratories following different operating procedures, were found to be quite different. The inconsistency of the measured viscosities makes data interpretation very difficult.…”
Section: Maximal Molecular Weight G/molmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy and repeatability of VR viscosity measurements are affected by the selection of viscometers and the experimental procedures followed by different operators [4,36]. A study published by Miller et al [4] indicated that heavy oil viscosities measured by different viscometers, or by the same type of viscometer but measured in different laboratories following different operating procedures, were found to be quite different. The inconsistency of the measured viscosities makes data interpretation very difficult.…”
Section: Maximal Molecular Weight G/molmentioning
confidence: 99%
“…The lower fluidity and volatility make vacuum residues difficult to analyze. For that reason, sometimes strange values for a VR's physicochemical properties are reported [4,5]. The proper preparation of a VR sample before analyzing is important to reduce the probability of misinterpretation of the obtained results [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these properties are directly involved in the optimization of oil refining operations, the determination and quality control of derivatives, the estimation of transport and storage conditions [4], the development of reservoir simulation processes [1], and the selection of a suitable oil recovery. However, measurements with conventional techniques take time, usually requiring tedious and expensive experimental processes, where accuracy decreases as oil viscosity increases, as equipment designs and protocols are focused on light and medium oils [5] [4] . Furthermore, human error in these measurements occurs more frequently and reflects a low reliability level in the characterization of oil, leading to failures in equipment designs for facilities, numerical simulations, and evaluation of reservoirs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy and repeatability of heavy oil viscosity measurements are not only affected by sample handling, storage, and cleaning procedures, but they are also affected by the selection of viscometers and the experimental procedures followed by different operators. A study published by Miller et al indicated that heavy oil viscosities measured by different viscometers or the same type of viscometer but measured in different laboratories following different operating procedures were found to be quite different. The inconsistency of the measured viscosities makes data interpretation and application to process designs difficult.…”
Section: Introductionmentioning
confidence: 99%